Impacts of Green Growth Policies on Labour Markets and Wage Income Distribution A General Equilibrium Application to Climate and Energy Policies - Chateau, Jean (OECD Environment Working Papers, 2018)
This paper explores the consequences on the labour markets of structural changes induced by decarbonisation policies. These policies are likely going to have consequences on labour-income distribution given i) existing rigidities in the labour markets, and ii) their different impacts on sectors and on job categories. These policies are analysed in a general equilibrium modelling framework, which includes interlinkages between different sectors and regions as well as five different categories of workers